Identification of Johnson-Cook Equation Constants using Finite Element Method - GRĄZKA, Michał; JANISZEWSKI, Jacek (Engineering Transactions, 2012)
The objective of this work is to develop an identification technique of the Johnson-Cook equation constants for copper Cu-ETP samples. In this paper we describe a method of constant identification using the Taylor impact test and finite element analysis. Nowadays the most popular method of constant identification method is the split Hopkinson pressure bar technique. This method is quite easy but needs very expensive laboratory equipment. To implement this method we have to make a lot of different tests in order to have enough information about dynamic properties. We decided to prepare an identification process algorithm using the Taylor impact test as a basic type of experimental and numerical simulation.